Patterns of automatic and reflective social information processing of adult male offenders and control group judging on ambiguous social situations - Lošakevičius, Andrius (Psichologija, 2015)
The social information processing (SIP) theory plays an important role in theoretical accounts of the social human behaviour. It provides significant advances in understanding social adjustment proposing that people, when faced with a social problem, engage in consecutive cognitive steps of information processing before enacting certain behaviour. However, the majority of studies include the research of children behaviour, and less is known regarding the SIP and social adjustment of adults. Besides, although there is a considerable evidence supporting the hypothesis that SIP is related to aggressive behaviour, this theory is criticized for its seemingly rational nature, and it is still not clear whether the structure proposed by the SIP model applies to the rational as well as the automatic behaviour when the social situation demands a rapid response. The aim of this study was to investigate the SIP patterns of adult male offenders and control group participants under different circumstances – when the social situation requires a rapid response and when there is time to rationally process the information. In total, 90 (57 convicted for various crimes and 33 – the control group) men aged 20 to 63 participated in the study. A structured interview was conducted after the participants had been presented with short video vignettes of the social interaction.The results showed significant differences between offenders and control group participants when recalling the social situations determining the goal the protagonist would set himself in the situation and evaluating a possible response of the protagonist. Moreover, when responding immediately, both offenders and the control group participants generated different answers as compared to those when providing reflective responses in each of the step of the SIP model. When responding immediately, a participant recalled less situational cues (p ≤ 0.05), and more of them were subjectively distorted (p ≤ 0.05), provided more hostile interpretations of the situation (p ≤ 0.05), and more often determined hostile goals for the protagonist. Besides, participants provided more hostile behaviour alternatives for the protagonist (p ≤ 0.05) and more often indicated that the protagonist was to choose a hostile way to react (p ≤ 0.05). The implications of these findings for the aggressive adult problem-solving behaviour are discussed.
Keywords: social information processing; adult offenders; automatic and reflective response; antisocial behaviour